IMF Staff Papers, Volume 46, No. 1. (IMF Staff Papers; IMF Staff Papers, 1999)
This economic journal contains theoretical and empirical analyses of varous macroeconomic issues. The studies are prepapred by IMF research staff or consultants. Subjects covered inclulde balance of payments and exchange rates, monetary systems and policies, public finances, international trade, economic growth, and some sectoral analyses. The last issue of the year contains an index to the volume. Approximately 200 pages in each issue.